Achieving superior electromagnetic wave absorbers through the novel metal-organic frameworks derived magnetic porous carbon nanorods. (April 2019) - Wu, Nannan; Xu, Dongmei; Wang, Zhou; Wang, Fenglong; Liu, Jiurong; Liu, Wei; Shao, Qian; Liu, Hu; Gao, Qiang; Guo, Zhanhu
Abstract: High absorption capacity and broad absorption bandwidth electromagnetic wave (EMW) absorption materials (namely, EMW absorbers) are highly desirable due to the interference with electronics and harms on human beings' health. In search for rational design on nanostructured absorbers, we have synthesized and demonstrated the rod-shape composites with Fe-containing magnetic nanoparticles (Fe3 O4, Fe3 C and Fe NPs) embedded into nano-porous carbon (NPC) through pyrolysis of Fe-based metal-organic frameworks (MOFs). The morphologies, compositions, and graphitization degree of the Fe-MOFs derived magnetic NPC nanorods can be effectively controlled via adjusting the pyrolysis temperatures. The graphitization level has a significant influence on the permittivity of the composites upon variation of pyrolysis temperatures, thereby a tunable electromagnetic wave (EMW) absorption is observed. Consequently, the resulting magnetic NPC nanorods obtained at pyrolysis temperature of 600 and 700 °C exhibit the most remarkable EMW absorption performance with a strong reflection loss of −52.9 dB and broad effective bandwidth ( f e ) of 4.64 GHz at 3.07 mm. With a thickness of 3.5 mm, the f e for the magnetic NPC nanorods at 600 °C covers the whole X-band from 7.92 to 12.48 GHz. The noticeable EMW absorption performances have been greatly enhanced compared to those reported Fe3 O4 based absorbers, owing to the synergy of multiple components and the porous structures inherited from MOFs. Graphical abstract: Image 1